RULING DUE TO BANKRUPTCY ASSETS DEBTORS BEYOND AREAS IN INDONESIA - Imam Syaifullah; Surya Sakti Megantoro (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2021)
The purpose of this study is to examine the consequences of bankruptcy decisions on debtor assets outside the territory of Indonesia and to see the extent to which the bankruptcy law provides protection to creditors from debtors whose assets are located outside the territory of Indonesia. This is Normative legal Research with a statutory approach, a conceptual approach and a comparative approach.The results and discussion concluded that the bankruptcy decision handed down by the Commercial Court in Indonesia could have an impact on the debtor’s assets outside the territory of Indonesia in accordance with Article 21 of the Bankruptcy Law. The issue of execution is hindered by the principle of territoriality from other countries. The bankruptcy law has not fully provided legal protection for creditors if the debtor has assets outside the territory of Indonesia, as a way for curators to carry out private selling. Indonesia should adopt the Uncitral Model Law on crossborder insolvency (1997) or enter into international agreements, either bilateral or multilateral.